Pembentukan Karakter Religius Melalui Ibadah Shalat Dhuha - Ade Pranata; Sri Haryanto; Vava Imam Agus Faisal (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This thesis aims to determine the formation of religious character through dhuha prayer worship of students at SMP Negeri 1 Pagedongan Banjarnegara, as well as the obstacles and solutions faced. This research is a type of descriptive qualitative research, while the subjects of the study were students of SMP Negeri 1 Pagedongan. Data collection was carried out through interview methods, observations and documents presented in a deductive inductive manner. Data analysis was carried out by interactive analysis, where the three components of analysis, namely data reduction, data presentation and drawing conclusions, were carried out interactively with qualitative descriptive analysis techniques. The results of the study indicate that 1) The formation of religious character through dhuha prayer worship at SMP Negeri 1 Pagedongan is carried out by students continuously and consistently every day. 2) The obstacles to the formation of religious character through dhuha prayer worship at SMP Negeri 1 Pagedongan are the lack of awareness in students to apply religious character through dhuha prayer worship and the lack of support from parents at home and the less than good community environment, lack of time to hold dhuha prayer worship activities at school, lack of supporting facilities and infrastructure in dhuha prayer worship activities. 3) The solution to the obstacles in forming religious character through Dhuha prayer at SMP Negeri 1 Pagedongan is to create a program aimed at instilling religious values ​​by involving all elements in the school.